Demanding energy space, time and change - Hui, Allison; Day, Rosie; Walker, Gordon (Palgrave Macmillan, 2018)
1. Demanding Energy: An Introduction -- Part 1 - Making Connections -- 2.Demanding Connectivity, Demanding Charging: The Co-production of Mobile Communication Between Electrical and Digital Infrastructures -- 3. Constructing Normality Through Material and Social Lock-in: The Dynamics of Energy Consumption Among Geneva’s More Affluent Households -- 4. Understanding Temporariness Beyond the Temporal: Greenfield and Urban Music Festivals and their Energy Use Implications -- Part 2 - Unpacking Meanings -- 5. Towards a ‘Meaning’-ful Analysis of the Temporalities of Mobility Practices: Implications for Sustainability -- 6. Being at Home Today: Inhabitance Practices and the Transformation and Blurring of French Domestic Living Spaces -- Part 3 - Situating Agency -- 7. The Car as a Safety-net: Narrative Accounts of the Role of Energy Intensive Transport in Conditions of Housing and Employment Uncertainty -- 8. The Tenuous and Complex Relationship Between Flexible Working Practices and Travel Demand Reduction -- 9. Leisure Travel and the Time of Later Life -- Part 4 - Tracing Trajectories -- 10. Changing Eating Practices in France and Great Britain: Evidence from Time Use Data and Implications for Direct Energy Demand -- 11. Paths, Projects and Careers of Domestic Practice: Exploring Dynamics of Demand over Biographical Time -- 12. Demanding Business Travel: The Evolution of the Timespaces of Business Practice -- Part 5 - Shifting Rhythms -- 13. Demand Side Flexibility and Responsiveness: Moving Demand in Time Through Technology -- 14. Reducing Demand for Energy in Hospitals: Opportunities for and Limits to Temporal Coordination -- Part 6 - Researching Demand -- 15. Identifying Research Strategies and Methodological Priorities for the Study of Demanding Energy
Enthält 15 Beiträge